Introduction to aquaculture management - Creative Educational Video, Inc. (Lubbock, TX : CEV Multimedia, 2009)
A brief look at the aquaculture industry and some of the key factors involved in successfully managing a aquacultural environment.
Fakulti Perubatan Veterinar.
Keywords: Aquaculture industry; Aquaculture